Recycled railway corridors: an urban design perspective - Froggatt, Thomas (2017)
In order to present an urban design perspective on recycled railway corridors this research considers the importance of place qualities to selected regional and neighbourhood transit contexts, also the spatial implications of a variety of certain differing transit modes are reviewed. This examination considers normative urban design criteria in relation to concepts of sustainable, transit-supportive built environments. This notion required a conceptual framework which accommodates the sophisticated and subjective aspects of regional design. Further, a visual methodology capable of accumulating significant quantities of data relevant to urban design was requisite. A qualitative case study strategy of inquiry was therefore adopted. Three UK recycled railway corridors were selected as case studies and considered independently and interdependently. This comparative analysis was predicated upon a variety of sources; archival, documentary and observational. This research uncovered urban design truths in the empirical context of recycled railway corridors. A high proportion of the instances examined in this research illustrate perfunctory urban design responses to public transit spaces, both in the regional and neighbourhood contexts. These instances were evocative of influences that prompt homogenisation in the anatomy of the built environment, with the automobile-dominated landscape showing prevalence. In these instances, normative urban design qualities were largely absent from the public realm. In lieu of these qualities ‘anywhere’ design responses, that failed to address issues of authenticity and place specificity, occupied those important spaces that relate to the public transit systems. However, this condition was not ubiquitous. This research examined instances where careful interdisciplinary ‘joined-up thinking’ has led to a set of place specific, transit supportive urban designs. Here, the opportunities inherent at the convergence of public transit systems and the human scale public realm have been taken advantage of. This has been achieved through the consideration of issues such as palimpsest, rootedness and place specificity, which have resulted in exemplars of bespoke, transit supportive urban designs.